Fostering in situ conservation of wild relatives of forage crops - Kägi, Christina; Petitpierre, Blaise; Meyer, Philipp; Lötscher, Yvonne; Eggenberg, Stefan; Aubry, Sylvain (Frontiers in Plant Science, 2023)
Most plant conservation strategies generally overlook the intra-specific genetic diversity of crop gene pools. Focusing on forage crops and their wild relatives, we present a novel approach to address the conservation of these species on meadows. Two-thirds of Swiss agricultural land is green land, mostly used for forage purposes, and their genetic diversity is being threatened. We focused here on eight plant associations gathering at least 18 taxa considered priority crop wild relatives of forage crops. Since 2020, about 1,217 high-quality surfaces (representing 1,566 hectares) nationwide have been integrated into an innovative auction-based policy instrument dedicated to conserving these populations. Here, we report the benefits and hurdles of implementing this bottom-up approach and try to estimate the quality of conservation of the forage plants’ CWR gene pool. Although we focus on the Swiss case, our approach to in situ conservation offers opportunities to effectively guide conservation in other contexts. We also discuss possible ways to improve CWR conservation policy, particularly the need to better consider the populations and habitat levels.